Crotonylation impedes c-Myc oncogenic activity - Nicholas J. Wallbillich; Peng Liao; Rashmi Srivastava; Jia Fan; Shelya X. Zeng; Hua Lu (Proceedings of the National Academy of Sciences, 2026)
c-Myc, an important oncoprotein, is highly regulated via posttranslational modifications. Herein, we report c-Myc crotonylation, an acylation stemming from the short-chain fatty acid crotonate. By biochemical analyses and high-resolution mass spectrometry sequencing, we showed that c-Myc is crotonylated at several lysine residues, spanning its middle to C termini. Mutation of these crotonylation sites conferred cells with a significant proliferative advantage with two key residues at K289 and K298 identified. Mutation of these lysine residues increased the binding of the mutant c-Myc to its regulator S-phase-kinase-associated protein 2 (Skp2) that can enhance c-Myc transcriptional activity while degrading it afterward. Interestingly, the K298N mutation was identified in some primary human tumors via screening human cancer database. More interestingly, this cancer-derived mutant c-Myc displayed more oncogenic activity than did wild type c-Myc in vitro and in vivo, in part, by partnering with Skp2. Together, these results demonstrate that crotonylation can impair the oncogenic activity of c-Myc.